Heterologous Expression of a Novel Zoysia japonica C2H2 Zinc Finger Gene, ZjZFN1, Improved Salt Tolerance in Arabidopsis - Teng, Ke; Tan, Penghui; Guo, Weier; Yue, Yuesen; Fan, Xifeng; Wu, Juying (Frontiers in Plant Science, 2018)
Growing evidence indicates that some grass species are more tolerant to various abiotic and biotic stresses than many crops. Zinc finger proteins play important roles in plant abiotic and biotic stresses. Although genes coding for these proteins have been cloned and identified in various plants, their function and underlying transcriptional mechanisms in the halophyte Zoysia japonica are barely known. In the present study, ZjZFN1 was isolated from Z. japonica using RACE method. Quantitative real time PCR results revealed that the expression of ZjZFN1 was much higher in leaf than in root and stem tissues, and induced by salt, cold or ABA treatment. The subcellular localization assay demonstrated that ZjZFN1 was localized to the nucleus. Expression of the ZjZFN1 in Arabidopsis thaliana improved seed germination and enhanced plant adaption to salinity stress with improved percentage of green cotyledons and growth status under salinity stress. Physiological and transcriptional analyses suggested that ZjZFN1 might, at least in part, influence reactive oxygen species accumulation and regulate the transcription of salinity responsive genes. Furthermore, RNA-sequencing analysis of ZjZFN1-overexpressing plants revealed that ZjZFN1 may serve as a transcriptional activator in the regulation of stress responsive pathways, including phenylalanine metabolism, α-linolenic acid metabolism and phenylpropanoid biosynthesis. Taken together, these results provide evidence that ZjZFN1 is a potential key player in plants’ tolerance to salt stress, and it could be a valuable gene in Z. japonica breeding projects.